Deuterium–deuterium fusion in nanowire plasma driven with a nanosecond high-energy laser - Xi, Xiaofeng; Lv, Chong; Ma, Wenjun; Liu, Fulong; Kong, Defeng; Zhang, Xiaopeng; Zhang, Guoqiang; Sun, Wei; He, Chuangye; Deng, Xiangai; Ma, Zhiguo; Zhao, Jiarui; et al. (Frontiers in Physics, 2023)
Investigating the enhancement of the interaction between laser and plasma is crucial for fundamental and applied physics researches based on laser induced acceleration and nuclear reactions. The improvement of energy conversion efficiency resulting in increasing reaction yields has been extensively studied by the interaction of femtosecond (fs) or picosecond (ps) lasers with nanowire targets. However, the effects of nanosecond (ns) lasers interacting with nanowire targets on energy absorption and production yield remain unknown. To address this issue, we conducted a deuterium-deuterium fusion experiment based on the collision of two plasmas induced by the interaction of the kilo-Joule level nanosecond laser with nanowire targets.The experimental results of neutron detection indicate that the yields of nanowire targets remain at the same level as those of planar targets. We have used the counter-streaming collisionless plasma model to perform a numerical analysis of the output of nuclear reaction products at the center-of-mass energy (E c.m. ) values between 10 keV and 30 keV, and the calculation results are in good agreement with the experimental results. In addition, a magneto-hydrodynamic numerical simulations has also been performed. It shows that the critical density of the target's surface, which forms on the picosecond time scale, blocks the absorption of laser energy with 1 Xi et al.nanosecond pulse length. Consequently, both our experimental and simulating results indicate that the enhancement factor is limited when a target with a spatial period less than µm is used in conjunction with a ns laser. Therefore, additional research is highly desirable to develop a target structure that can improve the efficiency of energy conversion between lasers and the target.